Tire
Patent Information
- Application Number
- CN202610200813.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-01-16
- Filing Date
- 2026-02-11
- Publication Date
- 2026-10-23
AI Technical Summary
[0022]根据本发明,能够实现耐磨损性能与耐掉块性能的综合性能进一步提高。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a tire. Background Technology
[0002] In recent years, various proposals have been put forward (for example, patent documents 1 to 5) in order to meet the requirements for improving the wear resistance and chip resistance of tires installed on vehicles, with the expectation of further improving performance.
[0003] [Existing Technical Documents]
[0004] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 2019-218481
[0006] [Patent Document 2] Japanese Patent Application Publication No. 2020-59769
[0007] [Patent Document 3] Japanese Patent Application Publication No. 2021-25006
[0008] [Patent Document 4] Japanese Patent Application Publication No. 2022-121896
[0009] [Patent Document 5] Japanese Patent Application Publication No. 2024-2911 Summary of the Invention
[0010] [The problem the invention aims to solve]
[0011] The objective of this invention is to further improve the overall performance of tires in terms of wear resistance and sharding resistance.
[0012] [Methods for solving the problem]
[0013] This invention relates to a tire, characterized in that,
[0014] It is a tire with a tread.
[0015] The tread portion has a tread rubber layer with a thickness (mm) formed at a ratio C (%) relative to the total thickness (mm) of the tread portion.
[0016] The rubber layer of the driving surface is formed using a rubber composition that contains less than 25% by weight of styrene-butadiene rubber (SBR) in the rubber component, and, relative to 100 parts by weight of the rubber component, contains more than 90 parts by weight of silica and more than 55 parts by weight of resin component.
[0017] The complex elastic modulus of the rubber layer on the driving surface is 0°E. *The loss tangent (tanδ) of the rubber layer at 0℃ and -20℃ tanδ (tanδ, -30℃ tanδ, -40℃ tanδ) satisfies the following equation (1), and the complex elastic modulus at 0℃ E * (MPa) was measured at a temperature of 0℃, a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of elongation. The loss tangents (0℃ tanδ, -20℃ tanδ, -30℃ tanδ, -40℃ tanδ) were measured at a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of tension, at temperatures of 0℃, -20℃, -30℃, and -40℃.
[0018] Furthermore, B1, as shown in equation (1), satisfies equation (2) with the ratio C (%).
[0019] B1[={(-40℃tanδ)+(-30℃tanδ)+(-20℃tanδ)}×0℃tanδ / 0℃E * ]≥0.060 (1)
[0020] B1×C>1.0 (2)
[0021] [Invention Effects]
[0022] According to the present invention, the overall performance of wear resistance and spalling resistance can be further improved. Detailed Implementation
[0023] [1] Features of the tires involved in this invention
[0024] The features of the tire involved in this invention will first be described.
[0025] 1. Overview
[0026] The tire of the present invention is a tire having a tread, the tread having a tread rubber layer having a thickness (mm) of a ratio C (%) relative to the total thickness (mm) of the tread. The tread rubber layer is formed using a rubber composition that contains less than 25% by mass of styrene-butadiene rubber (SBR) in the rubber composition, and, relative to 100 parts by mass of the rubber composition, contains more than 90 parts by mass of silica and more than 55 parts by mass of resin.
[0027] Furthermore, the complex elastic modulus of the rubber layer on the driving surface is 0°CE. *(MPa), and the loss tangent (0℃tanδ, -20℃tanδ, -30℃tanδ, -40℃tanδ) satisfies the following equation (1), measured at a temperature of 0℃, a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of elongation, measured at a temperature of 0℃, -20℃, -30℃, and -40℃ under the conditions of a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of tension; and, B1 shown in the following equation (1) satisfies the following equation (2) with the above ratio C (%).
[0028] B1[={(-40℃tanδ)+(-30℃tanδ)+(-20℃tanδ)}×0℃tanδ / 0℃E * ]≥0.060 (1)
[0029] B1×C>1.0 (2)
[0030] By incorporating these features, as described below, the overall performance of the tire, including its wear resistance and sharding resistance, can be further improved.
[0031] 2. The principle underlying the performance effect in tires involved in this invention.
[0032] The principle underlying the aforementioned performance effects in the tires involved in this invention can be considered as follows.
[0033] (1) Contains low-styrene SBR
[0034] As described above, the rubber composition of the tread rubber layer of the tire of the present invention contains styrene-butadiene rubber (SBR) with a styrene content of less than 25% by mass.
[0035] Because SBR with a low styrene content, specifically less than 25% by mass (low-styrene SBR), has a lower glass transition temperature (Tg), the Tg of the rubber component in the tread rubber layer of the tire tread can be reduced by incorporating low-styrene SBR into the tread rubber layer. Furthermore, the formation of tiny styrene regions in the rubber matrix through low-styrene SBR improves the polymer's mobility, allowing for more flexible movement.
[0036] These results can be considered to make cracking, which is the cause of wear and spalling, less likely to occur, thereby achieving a combination of wear resistance and spalling resistance.
[0037] Furthermore, it can be argued that the small, flexible styrene regions generate heat more easily through mutual friction, thus mitigating the input energy and improving resistance to chipping.
[0038] Furthermore, it can be considered that by mixing low-styrene SBR and forming small styrene regions, it is easy for them to interact with the filler, which can give full play to the reinforcing effect, thus increasing the breaking energy and improving the wear resistance.
[0039] (2) Contains silicon dioxide
[0040] In this invention, the rubber composition for the driving surface contains a large amount of silica as a reinforcing filler, which is greater than 90 parts by mass relative to 100 parts by mass of the rubber component. It can be considered that by containing such a large amount of silica, the interaction between the flexibly moving micro-styrene regions and the silica can achieve a comprehensive improvement in wear resistance and spalling resistance.
[0041] (3) Contains resin components
[0042] In this invention, the rubber composition for the driving surface contains, in addition to silica, a large amount of resin component in quantities greater than 55 parts by mass relative to 100 parts by mass of the rubber component. It can be considered that by containing such a large amount of resin component, the destructive energy is increased, thereby improving wear resistance.
[0043] (4) Control of B1
[0044] The loss tangent tanδ can be considered as an indicator of energy absorption performance. The larger the value, the easier it is to generate sufficient energy loss in the rubber composition, thereby suppressing defects caused by rubber deformation and improving the resistance to shavings.
[0045] On the other hand, the complex elastic modulus E can be considered as * (MPa) is an indicator of the rigidity of a rubber composition. The smaller the value, the softer the rubber becomes, thereby inhibiting slippage between the rubber and the road surface and improving wear resistance.
[0046] Based on the above information, to achieve a comprehensive improvement in both wear resistance and spalling resistance, it is necessary to control the loss tangent tanδ and the complex elastic modulus E. * The balance is achieved by increasing the loss tangent (tanδ) in the rubber composition to a certain extent to improve its resistance to chipping, while on the other hand, it is necessary to reduce the complex elastic modulus E to a certain extent. * This improves wear resistance.
[0047] Furthermore, it is believed that specific research results show that by appropriately controlling the [{(-40℃tanδ) + (-30℃tanδ) + (-20℃tanδ)} × 0℃tanδ} / 0℃E * A B1 value of 0.060 or higher indicates a comprehensive improvement in both wear resistance and spalling resistance.
[0048] In addition, when calculating B1 above, the complex elastic modulus and loss tangent can be measured, for example, using a viscoelasticity measuring device such as the "EPLEXOR (registered trademark)" manufactured by GABO.
[0049] Furthermore, the aforementioned loss tangent tanδ and complex elastic modulus E * The amount and type of reagents (especially rubber components, fillers, resin components, sulfur, and vulcanization accelerators) compounded in the rubber composition (surface rubber layer, base rubber layer) can be adjusted. For example, increasing the SBR content, increasing the content of fillers or resin components can increase the loss tangent tanδ; increasing the amount of fillers, increasing the amount of sulfur, or increasing the amount of vulcanization accelerators can increase the complex elastic modulus E. * .
[0050] (5) Relationship between driving surface ratio and B1
[0051] Furthermore, in this invention, the product of B1 and the travel surface ratio C, B1×C, is controlled to be greater than 1.0. Therefore, it is considered that cracking, which is a cause of wear and chipping, is unlikely to occur, and the overall performance of wear resistance and chipping resistance can be further improved. That is, it can be considered that by increasing B1 as described above, the overall performance of wear resistance and chipping resistance can be improved. In addition, by increasing the travel surface ratio and increasing the thickness of the travel surface rubber layer, the accumulation of heat during driving can be sufficiently suppressed, further improving the overall performance of wear resistance and chipping resistance.
[0052] It can be considered that in this invention, by making the above-mentioned effects work synergistically, the overall performance of tire wear resistance and chipping resistance can be further improved.
[0053] [2] A more preferred embodiment of the tires involved in the present invention
[0054] The tires involved in this invention can achieve further and greater effects by employing the following methods.
[0055] 1. Low-styrene SBR
[0056] As described above, by using low-styrene SBR with a styrene content of less than 25% by mass, it is possible to achieve a comprehensive improvement in both wear resistance and spalling resistance. Furthermore, with the reduction in styrene content, the glass transition temperature (Tg) also decreases further, making it difficult for cracking, which is a cause of wear and spalling, to occur, thus further improving the overall performance of both wear resistance and spalling resistance.
[0057] In this invention, the styrene content of the low-styrene SBR is more preferably 20% by mass or less, further preferably 15% by mass or less, and particularly preferably 10% by mass or less. On the other hand, as a lower limit, it is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 7% by mass or more.
[0058] Here, "low-styrene SBR containing less than 25% by mass" means that the total styrene content in the SBR is less than 25% by mass.
[0059] That is, when the rubber component contains one styrene-containing polymer (SBR), it means that the amount of styrene is less than 25% by mass; when the rubber component contains multiple styrene-containing polymers (SBR), it means that the amount of styrene, calculated by summing the product of the amount of styrene in each polymer (by mass%) and the amount of that polymer in the blend relative to 100 parts by mass of the rubber component (by mass), is less than 25% by mass.
[0060] More specifically, when 100 parts by mass of rubber composition contain S1% by mass of SBR1 (X1 parts by mass) and S2% by mass of SBR2 (X2 parts by mass) of styrene, it means that the amount of styrene calculated by the formula (S1×X1)+(S2×X2)} / (X1+X2) is less than 25% by mass.
[0061] Alternatively, the amount of styrene in the rubber composition can be determined by solid-state nuclear magnetic resonance (SMR) or Fourier transform infrared spectrophotometry (FTIR) in the vulcanized rubber composition, and then calculated.
[0062] The content of low-styrene SBR in 100 parts by weight of the rubber component is preferably greater than 50 parts by weight, more preferably greater than 60 parts by weight, even more preferably greater than 65 parts by weight, and particularly preferably greater than 70 parts by weight. As an upper limit, for example, it is preferably less than 90 parts by weight, more preferably less than 85 parts by weight, and even more preferably less than 80 parts by weight.
[0063] Furthermore, the glass transition temperature (Tg) of the low-styrene SBR is preferably below -25°C, more preferably below -40°C, even more preferably below -55°C, and particularly preferably below -70°C. On the other hand, as a lower limit, it is preferably above -95°C, more preferably above -90°C, even more preferably above -85°C, and particularly preferably above -80°C.
[0064] Furthermore, the glass transition temperature of SBR can be determined based on the temperature distribution curve of tanδ measured using a viscoelasticity measuring device such as the GABO "EPLEXOR" series. Specifically, the temperature distribution curve of tanδ is measured under the conditions of a frequency of 10 Hz, an initial strain of 10%, an amplitude of ±0.5%, and a heating rate of 2 °C / min. The temperature corresponding to the maximum tanδ value in the range of -100 °C to 40 °C is set as the glass transition temperature (Tg).
[0065] Furthermore, if there are two or more points with the maximum tanδ value within the range of -100°C to 40°C, the point with the lowest temperature is set as the glass transition temperature (Tg). For example, in this invention, if the peak value of tanδ is within the range of -100°C to 40°C, then according to the above definition, this peak temperature is the glass transition temperature (Tg). Furthermore, for example, if a temperature distribution curve is obtained where the peak value of tanδ is in a region below -100°C and within the range of -100°C to 40°C, and tanδ gradually decreases with increasing temperature, then according to the above definition, the glass transition temperature (Tg) is -100°C.
[0066] 2. Silicon dioxide
[0067] By including a large amount of silica relative to 90 parts by mass per 100 parts by mass of the rubber component, as described above, a comprehensive improvement in both wear resistance and spalling resistance can be achieved. The silica content relative to 100 parts by mass of the rubber component is more preferably greater than 93 parts by mass, further preferably greater than 95 parts by mass, even more preferably greater than 98 parts by mass, and particularly preferably 100 parts by mass or more. On the other hand, there is no particular upper limit, but it is preferably less than 190 parts by mass, more preferably less than 180 parts by mass, further preferably less than 170 parts by mass, and particularly preferably less than 160 parts by mass.
[0068] 3. Resin composition
[0069] By containing a large amount of resin component, greater than 55 parts by mass relative to 100 parts by mass of the rubber component as described above, a comprehensive improvement in wear resistance and spalling resistance can be achieved. More preferably, it is greater than 60 parts by mass, further preferably 65 parts by mass or more, and particularly preferably 68 parts by mass or more. As an upper limit, there is no particular limitation, but preferably less than 85 parts by mass, more preferably less than 80 parts by mass, further preferably less than 75 parts by mass, and particularly preferably less than 70 parts by mass.
[0070] Specific resin components include, for example, rosin-based resins, styrene-based resins, coumarone-based resins, terpene-based resins, C5 resins, C9 resins, C5C9 resins, and acrylic resins, but C5 resins and C9 resins are more preferred among these, and dicyclopentadiene resin (DCPD resin) and AMS resin (α-methylstyrene resin) are particularly preferred. Dicyclopentadiene resin may also be hydrogenated.
[0071] 4. Relationship between SBR quantity and flatness ratio
[0072] Aspect ratio is the ratio of tire section height to section width. A higher aspect ratio (higher aspect ratio) indicates a smaller contact area with the road surface, thus further improving the overall performance of wear resistance and anti-scratching properties. Conversely, it can be argued that by using SBR containing low-styrene, as mentioned above, the overall performance of wear resistance and anti-scratching properties can be further improved.
[0073] Therefore, it can be considered that increasing the SBR content C in 100 parts by mass of the rubber component can improve the rubber composition. S The product of (parts by mass) and tire aspect ratio A (%) (C) S (×A), which can further improve the overall performance of wear resistance and spalling resistance.
[0074] Specifically, C S ×A is preferably greater than 2000, more preferably greater than 2500, even more preferably greater than 3000, and particularly preferably greater than 3500. As an upper limit, there is no particular limitation; for example, it is preferably less than 6500, more preferably less than 6000, and even more preferably less than 5500.
[0075] 5. Relationship between silica content and negative profile ratio
[0076] Negative profile ratio refers to the ratio (%) of the total open area of multiple grooves to the virtual contact area of the tread completely filling all multiple grooves (the total contact area of the tire around its entire circumference when the tread with a camber angle of 0° is pressed against a plane under normal internal pressure and normal load conditions, with the tread completely filling all multiple grooves as the tire is in a normal state). It can be considered that the smaller this ratio (lower negative profile ratio), the larger the contact area with the road surface, which can generate greater energy loss across the entire tread surface, and can further improve the overall performance of wear resistance and anti-scratching performance.
[0077] On the other hand, it can be considered that even if silica contains a large amount of reinforcing filler, as mentioned above, it is possible to further improve the overall performance of wear resistance and spalling resistance.
[0078] Therefore, it can be considered that by appropriately controlling the amount of silica C relative to 100 parts by mass of the rubber component... SI The ratio of (parts by mass) to the negative profile ratio N (%) of the tire (C) SI / N), which can achieve a comprehensive improvement in both wear resistance and spalling resistance. Specifically, the ratio (C SI The ratio ( / N) is preferably greater than 3, more preferably greater than 3.1. There is no particular upper limit, but for example, it is preferably less than 4.5, more preferably less than 4.
[0079] Furthermore, the aforementioned negative profile ratio can be determined based on the grounding shape under normal rim, normal internal pressure, and normal load conditions.
[0080] Specifically, the ground contact shape can be obtained by assembling a tire onto a standard rim, applying standard internal pressure, allowing it to stand at 25°C for 24 hours, then applying ink to the tire tread surface, subjecting the tire to a standard load, and pressing it onto a cardboard (camber angle 0°), allowing the ink to transfer onto the cardboard. The tire is then rotated 72° circumferentially, resulting in 5 transfer points. That is, 5 ground contact shapes are obtained. For the 5 ground contact shapes, the average of the maximum axial length of the tire is set as L, and the average of the length perpendicular to the axial direction is set as W. The negative profile ratio (%) is calculated as [1 - {Average area of the 5 ground contact shapes (ink portions) transferred to the cardboard / L × W)} × 100 (%). Here, the average length and area are a simple average of the 5 values, where L × W represents the area of the virtual surface obtained by connecting the blank areas of the main groove and transverse groove when the ground contact shape is obtained.
[0081] Here, "normal condition" means: the tire is assembled on a normal rim and filled with normal internal pressure, and is unloaded.
[0082] "Standard rim" refers to the rim specified for each tire within a standard system that includes the standards upon which the tire is based. For example, it refers to the standard rim with applicable dimensions listed in the JATMA (Japan Automobile Tire Association) Yearbook, the "Measuring Rim" listed in the ETRTO (European Tyre and Rim Technical Organization) Standards Manual, and the "Design Rim" listed in the TRA (Tire and Rim Association, Inc.) Yearbook. These should be referenced in the order of JATMA, ETRTO, and TRA, and if applicable dimensions are available, their standards should be followed. Furthermore, for tires not specified in the aforementioned standards, it refers to the rim with the smallest rim width among the smallest rim diameters that can be assembled and maintain internal pressure (i.e., no air leakage between the rim and tire).
[0083] Furthermore, "standard internal pressure" refers to the air pressure specified for each tire within the standard system upon which the tire is based. This includes the maximum value recorded in JATMA's "Maximum Air Pressure," ETRTO's "Inflation Pressure," and TRA's table "Tire Load Limits at Various Cold Inflation Pressures," referenced in the order of JATMA, ETRTO, and TRA. If an applicable size is specified, that standard should be followed. For tires not specified in the aforementioned standards, it refers to the standard internal pressure (of which 250 kPa or higher) for other tire sizes (those specified in the standards) using the aforementioned standard rim as the standard rim. Additionally, when multiple standard internal pressures of 250 kPa or higher are recorded, the minimum value is used.
[0084] Furthermore, "standard load" refers to the load specified for each tire within a standard system that includes the standard on which the tire is based. It refers to the maximum mass allowed to be applied to the tire, specifically the maximum value recorded in JATMA's "Maximum Load Capacity," ETRTO's "Load Capacity," and TRA's "Tire Load Limits at Various Cold Inflation Pressures." Similar to the cases of "standard rim" and "standard internal pressure," it is referenced in the order of JATMA, ETRTO, and TRA, following the applicable standard if applicable dimensions are available. For tires not specified in the standard, the standard load W is calculated using the following methods. L .
[0085] V = {(Dt / 2)} 2 -(Dt / 2-Ht) 2}×π×Wt
[0086] W L =0.000011×V+175
[0087] W L Standard load (kg)
[0088] V: Virtual volume of the tire (mm) 3 )
[0089] Dt: Tire outer diameter Dt (mm)
[0090] Ht: Tire section height (mm)
[0091] Wt: Tire cross-sectional width (mm)
[0092] 6. Relationship between resin content and negative profile ratio
[0093] Similarly, it can be considered that by appropriately controlling the amount of resin component C relative to 100 parts by mass of rubber component, the resin component can be effectively controlled. R (parts by mass), the ratio of the negative profile ratio N (%) in the tread surface of the tire (C) R / N), which can achieve a comprehensive improvement in both wear resistance and spalling resistance. Specifically, the ratio (C R The ratio ( / N) is preferably greater than 2.0, more preferably greater than 2.1, and even more preferably greater than 2.2. There is no particular upper limit, but for example, it is preferably less than 3.5, more preferably less than 3.0.
[0094] 7. Ratio of driving surface
[0095] The tread portion has a tread rubber layer. This tread rubber layer can be the outermost layer, with a base rubber layer inside, making it two layers; alternatively, it can have three or four or more layers. In this case, the ratio of the thickness of the tread rubber layer to the thickness of the tread portion (tread ratio) is preferably greater than 10%, more preferably 15% or more, even more preferably 20% or more, and particularly preferably 25% or more. This is considered to further improve the overall performance in terms of wear resistance and tread chipping resistance. There is no particular upper limit, but it is preferably 90% or less, more preferably 80% or less, and even more preferably 70% or less.
[0096] Furthermore, the thickness of the tread layer is preferably 5 mm or more, more preferably 6 mm or more, and even more preferably 8 mm or more. This is considered to improve the overall performance of wear resistance and anti-scratching properties. There is no particular limitation on the upper limit; for example, it is preferably 20 mm or less, more preferably 18 mm or less, and even more preferably 16 mm or less.
[0097] The tread rubber layer is not limited to the outermost tread rubber layer forming the tread surface. When there are two or more layers within 5 mm from the tread surface inward, at least any one layer needs to meet the conditions of the above-mentioned rubber composition.
[0098] Here, the thickness of the tread refers to the thickness of the tread on the equatorial plane of the tire in the radial section of the tire. When the tread is formed by a single rubber composition, it refers to the thickness of that rubber composition. When it is formed by a laminated structure of multiple rubber compositions, it refers to the total thickness of these layers.
[0099] For example, when there is a groove on the equatorial surface of the tire, it refers to the thickness from the intersection of the straight line connecting the outermost radial endpoint of the tire to the equatorial surface of the tire, to the innermost radial interface of the tread.
[0100] The thickness of the tread layer can be calculated by adding the thickness of the tread rubber layers (the sum of all layers if there are two or more) and the thickness of the base rubber layers (the sum of all layers if there are two or more). Here, "thickness of the tread rubber layers" refers to the thickness of the tread rubber layers on the tire equatorial plane in the tire's radial section. When there are grooves on the tire equatorial plane, it refers to the thickness from the intersection of the straight line connecting the outermost radial endpoint of the groove and the tire equatorial plane to the interface of the innermost base rubber layer in the tire's radial direction on the tread layer. Furthermore, "thickness of the base rubber layer" refers to the thickness from the interface with the tread rubber layers to the interface of the innermost radial direction on the tread layer. Additionally, "groove" refers to a groove on the outermost surface of the tread layer with an opening width of 3 mm or more and a depth of 3 mm or more.
[0101] Furthermore, the tread portion refers to the area that forms the contact patch of the tire, including the portion closer to the radial outer side of the tire than components containing fibrous materials such as the carcass, belt ply, and belt reinforcement ply. The thickness of the tread portion can be measured by setting a cross-section of the tire cut radially such that the bead portion conforms to the standard rim width.
[0102] 8. Particle size of silica
[0103] Considering factors such as ease of friction with the polymer, the particle size (average primary particle size) of silica is preferably 16 nm or less, more preferably 15 nm or less. It can be considered that by using small-particle-size silica, the contact frequency with the polymer (styrene region) of styrene-butadiene rubber (SBR) is increased, thereby further improving the overall performance of wear resistance and spalling resistance. As a lower limit, for example, there is no particular limitation, but it is preferably greater than 8 nm, more preferably greater than 10 nm.
[0104] In addition, the average primary particle size can be calculated by directly observing the silica extracted from the rubber composition cut from the tire using an electron microscope (TEM), calculating the cross-sectional diameter based on the area of each silica particle, and then taking the average value.
[0105] 9. Isoprene-based rubbers
[0106] In addition to low-styrene SBR, the rubber composition preferably also contains isoprene-based rubber. By including isoprene-based rubber in addition to low-styrene SBR, micro-layers of varying hardness can be mixed within the rubber phase, thereby improving both wear resistance and resistance to spalling. The isoprene-based rubber content in 100 parts by weight of the rubber composition is preferably greater than 3 parts by weight, more preferably greater than 5 parts by weight, and even more preferably greater than 10 parts by weight. On the other hand, as an upper limit, it is preferably less than 40 parts by weight, more preferably less than 35 parts by weight, even more preferably less than 30 parts by weight, and particularly preferably less than 25 parts by weight.
[0107] Specific isoprene-based rubbers include natural rubber (NR), modified natural rubber (modified NR), modified natural rubber (modified NR), and synthetic polyisoprene (isoprene rubber (IR), modified isoprene rubber (modified IR)), etc., but among these, NR with excellent strength is preferred. Furthermore, as NR, for example, materials commonly used in the tire industry such as SVR-L, SIR20, RSS#3, and TSR20 can be used.
[0108] [3] Implementation
[0109] The present invention will be specifically described below based on the embodiments.
[0110] 1. Rubber composition
[0111] In the tires of the present invention, the rubber composition forming the tread (including the driving surface rubber layer of the tread) (tread rubber composition) can be obtained by appropriately adjusting the type and amount of various compounding materials such as rubber components, fillers, softeners, vulcanizing agents and vulcanization accelerators described below.
[0112] (1) Compounding materials
[0113] (a) Rubber composition
[0114] As mentioned above, low-styrene SBR is used as a rubber component. Other rubber components used besides low-styrene SBR include isoprene rubber, butadiene rubber (BR), nitrile rubber (NBR) and other diene rubbers, butyl rubber and other butyl rubbers, and thermoplastic elastomers such as styrene-butadiene-styrene block copolymer (SBS) and styrene-butadiene block copolymer (SB), which are commonly used rubbers (polymers) in tire manufacturing.
[0115] (A) SBR
[0116] The weight-average molecular weight of the SBR is, for example, greater than 100,000 and less than 2,000,000. Furthermore, in this invention, as described above, the styrene content in the SBR composition is set to be less than 25% by mass. The vinyl content (1,2-bonded butadiene content) of the SBR is preferably, for example, greater than 5% by mass, and the upper limit is preferably less than 70% by mass. Moreover, the vinyl content of the SBR refers to the 1,2-bonded butadiene content within the SBR composition relative to the total butadiene portion. Furthermore, the structural identification of the SBR (determination of styrene content and vinyl content) can be performed, for example, using an apparatus from the JNM-ECA series manufactured by Nippon Egis Corporation.
[0117] There are no particular limitations on the type of SBR used; for example, emulsion-polymerized styrene-butadiene rubber (E-SBR) and solution-polymerized styrene-butadiene rubber (S-SBR) can be used. The SBR can be either unmodified or modified. Furthermore, hydrogenated SBR, which involves hydrogenating the butadiene portion of the SBR, can also be used. Hydrogenated SBR can be obtained by subsequently hydrogenating the BR portion of the SBR, or by copolymerizing styrene, ethylene, and butadiene to obtain the same structure. The SBR content per 100 parts by weight of the rubber component is as described above.
[0118] As a modified SBR, any SBR having functional groups that can interact with fillers such as silica is acceptable. Examples include end-modified SBRs (end-modified SBRs with the aforementioned functional groups at the ends) which are modified by a compound (modifier) having the aforementioned functional groups, main-chain modified SBRs with the aforementioned functional groups in the main chain, main-chain end-modified SBRs with the aforementioned functional groups in both the main chain and the ends (e.g., main-chain end-modified SBRs with the aforementioned functional groups in the main chain and at least one end modified by the aforementioned modifier), and end-modified SBRs modified (coupled) by a polyfunctional compound having two or more epoxy groups in the molecule and introducing hydroxyl or epoxy groups.
[0119] Examples of the aforementioned functional groups include, for example, amino, amide, silyl, alkoxysilyl, isocyanate, imino, imidazo, urea, ether, carbonyl, oxycarbonyl, mercapto, thioether, dithioether, sulfonyl, sulfinyl, thiocarbonyl, ammonium, imide, hydrazine, azo, diazo, carboxyl, nitrile, pyridyl, alkoxy, hydroxyl, oxygen, and epoxy groups. Furthermore, these functional groups may also have substituents.
[0120] Furthermore, as a modified SBR, for example, an SBR modified by a compound (modifier) represented by the following formula can be used.
[0121]
Chemical Formula 1
[0122]
[0123] Furthermore, in the formula, R 1 R 2 and R 3 Same or different, indicating alkyl, alkoxy, siloxy, acetal, carboxyl (-COOH), mercapto (-SH) or their derivatives. R 4 and R 5 Same or different, indicating hydrogen atoms or alkyl groups. R 4 and R 5 It can also bond and form a ring structure with nitrogen atoms. n represents an integer.
[0124] As a modified SBR modified by a compound (modifier) represented by the above formula, an SBR obtained by modifying the polymerization end (active end) of solution-polymerized styrene-butadiene rubber (S-SBR) by a compound represented by the above formula can be used (modified SBR, etc. as described in Japanese Patent Application Publication No. 2010-111753).
[0125] As R 1 R 2 and R 3Preferably, it is an alkoxy group (preferably with 1 to 8 carbon atoms, more preferably an alkoxy group with 1 to 4 carbon atoms). As R 4 and R 5 Preferably, it is an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms). n is preferably 1 to 5, more preferably 2 to 4, and even more preferably 3. Furthermore, R 4 and R 5 When the bond combines with a nitrogen atom to form a ring structure, a 4- to 8-membered ring is preferred. Furthermore, alkoxy groups also include cycloalkoxy groups (such as cyclohexyloxy) and aryloxy groups (such as phenoxy and benzyloxy).
[0126] Specific examples of the aforementioned modifiers include 2-dimethylaminoethyltrimethoxysilane, 3-dimethylaminopropyltrimethoxysilane, 2-dimethylaminoethyltriethoxysilane, 3-dimethylaminopropyltriethoxysilane, 2-diethylaminoethyltrimethoxysilane, 3-diethylaminopropyltrimethoxysilane, 2-diethylaminoethyltriethoxysilane, and 3-diethylaminopropyltriethoxysilane. These can be used alone or in combination of two or more.
[0127] In addition, modified SBRs can also be made using the following compounds (modifiers). As modifiers, these include, for example, polyglycidyl ethers of polyols such as ethylene glycol diglycidyl ether, glycerol triglycidyl ether, trimethylolethane triglycidyl ether, and trimethylolpropane triglycidyl ether; polyglycidyl ethers of aromatic compounds having two or more phenolic groups such as bisphenol A diglycidyl ether; polyepoxide compounds such as 1,4-diglycidylbenzene, 1,3,5-triglycidylbenzene, and polyepoxide liquid polybutadiene; tertiary amines containing epoxy groups such as 4,4'-diglycidyl diphenylmethylamine and 4,4'-diglycidyl dibenzylmethylamine; diglycidyl aniline, N,N'-diglycidyl... -4-glycidoxyaniline, diglycidyl-o-toluidine, tetraglycidyl-m-xylenediamine, tetraglycidylaminodiphenylmethane, tetraglycidyl-p-phenylenediamine, diglycidylaminomethylcyclohexane, tetraglycidyl-1,3-diaminomethylcyclohexane, and other diglycidylamino compounds; bis(1-methylpropyl)carbamoyl chloride, 4-morpholinocarbamoyl chloride, 1-pyrrolidinecarbamoyl chloride, N,N-dimethylcarbamoyl chloride, N,N-diethylcarbamoyl chloride, and other amino-containing acyl chlorides; 1,3-bis(glycidyloxypropyl)tetramethyldisiloxane, (3-glycidyloxypropyl)tetramethyldisiloxane, (3-glycidyloxypropyl)tetramethyldisiloxane, etc. Silane compounds containing epoxy groups, such as pentamethyldisiloxane; (trimethylsilyl)[3-(trimethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(triethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(tripropoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(tributoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldimethoxysilyl)propyl] sulfide, (trimethylsilyl)[3-(methyldiethoxysilyl)propyl] sulfide, (trimethylsilyl) Silane compounds containing thioether groups, such as [3-(methyldipropoxysilyl)propyl] sulfide and (trimethylsilyl)[3-(methyldibutoxysilyl)propyl] sulfide; N-substituted aziridine compounds such as ethyleneimine and propyleneimine; alkoxysilanes such as methyltriethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyltrimethoxysilane, N,N-bis(trimethylsilyl)-3-aminopropyltriethoxysilane, N,N-bis(trimethylsilyl)aminoethyltrimethoxysilane, and N,N-bis(trimethylsilyl)aminoethyltriethoxysilane.4-N,N-dimethylaminobenzophenone, 4-N,N-di-tert-butylaminobenzophenone, 4-N,N-diphenylaminobenzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-bis(diphenylamino)benzophenone, N,N,N',N'-bis(tetraethylamino)benzophenone, and other (thio)benzophenone compounds having amino and / or substituted amino groups; 4-N,N-dimethylaminobenzaldehyde, 4- N,N-Diphenylaminobenzaldehyde, 4-N,N-Divinylaminobenzaldehyde, and other benzaldehyde compounds having an amino group and / or substituted amino groups; N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, N-phenyl-2-pyrrolidone, N-tert-butyl-2-pyrrolidone, N-methyl-5-methyl-2-pyrrolidone, and other N-substituted pyrrolidones; N-methyl-2-piperidinone, N-vinyl-2-piperidinone, N-phenyl-2-piperidinone, and other N-substituted amino groups. Besides piperidinones; N-methyl-ε-caprolactam, N-phenyl-ε-caprolactam, N-methyl-ω-laurolactam, N-vinyl-ω-laurolactam, N-methyl-β-propiolactam, N-phenyl-β-propiolactam, and other N-substituted lactams, other examples include N,N-bis(2,3-epoxypropoxy)-aniline, 4,4-methylenebis(N,N-glycidylaniline), and tris(2,3-epoxypropyl)-1,3,5-triazine- 2,4,6-Triones, N,N-diethylacetamide, N-methylmaleimide, N,N-diethylurea, 1,3-dimethylethylidene urea, 1,3-divinylethylidene urea, 1,3-diethyl-2-imidazolinone, 1-methyl-3-ethyl-2-imidazolinone, 4-N,N-dimethylaminoacetophenone, 4-N,N-diethylaminoacetophenone, 1,3-bis(diphenylamino)-2-propanone, 1,7-bis(methylethylamino)-4-heptanone, etc. Furthermore, modification based on the above compounds (modifiers) can be carried out by known methods.
[0128] As an SBR (Self-Borne Blender), for example, SBR manufactured and commercially available by companies such as Sumitomo Chemical Co., Ltd., ENEOS MATERIALS Co., Ltd., Asahi Kasei Corporation, and Zeon Corporation of Japan can be used. Furthermore, SBR can be used alone or in combination of two or more types.
[0129] (B) Isoprene-based rubber
[0130] As described above, examples of isoprene-based rubbers include natural rubber (NR), modified natural rubber (modified NR), modified natural rubber (modified NR), and synthetic polyisoprene (isoprene rubber (IR), modified isoprene rubber (modified IR)). Furthermore, the content of isoprene-based rubber in 100 parts by mass of the rubber component is as described above.
[0131] For example, substances commonly used in the tire industry, such as SIR20, RSS#3, and TSR20, can be used as NR. For IR, there are no particular limitations; for example, substances commonly used in the tire industry, such as IR2200, can be used. Examples of modified NR include deproteinized natural rubber (DPNR) and high-purity natural rubber (UPNR); examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber; examples of modified IR include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These can be used individually or in combination of two or more.
[0132] (C)BR
[0133] In this invention, BR may be further included as needed. In this case, the BR content in 100 parts by weight of the rubber component is preferably 5 parts by weight or more, more preferably 7 parts by weight or more. On the other hand, it is preferably 20 parts by weight or less, more preferably 17 parts by weight or less.
[0134] The weight-average molecular weight of BR is, for example, greater than 100,000 and less than 2,000,000. The vinyl content of BR is, for example, greater than 1% by mass and less than 30% by mass. The cis content of BR is, for example, greater than 1% by mass and less than 98% by mass. The trans content of BR is, for example, greater than 1% by mass and less than 60% by mass.
[0135] There are no particular limitations on the type of BR used; BRs with high cis content (cis content ≥ 90%), low cis content, and BRs containing syndiotactic polybutadiene crystals can be used. BRs can be either unmodified or modified; modified BRs include those incorporating the aforementioned functional groups. These can be used individually or in combination. Furthermore, the cis content can be determined by infrared absorption spectroscopy.
[0136] As a BR (Brandinger), products from companies such as Ube Industries, Ltd., Enos Materials Co., Ltd., Asahi Kasei Corporation, and Zeon Corporation can be used.
[0137] (D) Other rubber components
[0138] In addition, as other rubber components, it may also contain rubbers (polymers) commonly used in tire manufacturing, such as nitrile rubber (NBR), as needed.
[0139] The raw materials (monomers) of the aforementioned synthetic rubbers such as SBR and BR can be substances derived from petroleum, or substances recycled from rubber products such as tires and non-rubber products such as polystyrene.
[0140] The monomer obtained through recycling (recycled monomer) is not particularly limited, and examples include butadiene derived from recycling and aromatic vinyl compounds derived from recycling. Examples of butadiene include 1,2-butadiene and 1,3-butadiene. Examples of aromatic vinyl compounds are not particularly limited, and examples include styrene. Preferably, butadiene derived from recycling (recycled butadiene) and / or styrene derived from recycling (recycled styrene) are used as raw materials.
[0141] There are no particular limitations on the manufacturing method of the recycled monomer. For example, it can be synthesized from recycled naphtha obtained by pyrolyzing rubber products such as tires. Furthermore, there are no particular limitations on the manufacturing method of the recycled naphtha. For example, rubber products such as tires can be pyrolyzed under high temperature and pressure, microwave pyrolysis can be used, or extraction can be performed after mechanical crushing.
[0142] Furthermore, the raw materials (monomers) for synthetic rubbers such as SBR and BR can also be substances derived from biomass. There are no particular limitations on what constitutes a biomass-derived monomer (biomass monomer), butadiene and aromatic vinyl compounds derived from biomass are examples. Examples of butadiene include 1,2-butadiene and 1,3-butadiene. Examples of aromatic vinyl compounds include styrene, etc. In addition, there are no particular limitations on the methods for manufacturing biomass monomers; for example, substances derived from biological and / or chemical and / or physical transformations of plants and animals can be listed. A representative example of biological transformation is microbial fermentation; examples of chemical and / or physical transformations include catalyst-based transformations, high-temperature transformations, high-pressure transformations, electromagnetic wave transformations, supercritical fluid transformations, and combinations thereof. Biomass sources for these monomers include sugar or wood, plant residues after the extraction of useful components, plant-derived ethanol, and biomass naphtha.
[0143] The term "biomass polymer" is not particularly limited to polymers synthesized from biomass monomer components, but examples include polybutadiene rubber synthesized from butadiene derived from biomass, and aromatic vinyl compound / butadiene copolymers synthesized from butadiene derived from biomass and / or aromatic vinyl compounds derived from biomass. Examples of such aromatic vinyl compound / butadiene copolymers include, for instance, styrene-butadiene rubber synthesized from butadiene derived from biomass and / or styrene derived from biomass.
[0144] Whether the polymer's raw materials are derived from biomass can be determined by the pMC (percent Modern Carbon) measured according to ASTM D6866-10.
[0145] pMC refers to: the sample14 C concentration relative to standard modern carbon (modern standard reference) 14 The ratio of C concentrations is used as an indicator of the biomass proportion of the compound (rubber). The significance of this value is described below.
[0146] One mole of carbon atoms (6.02 × 10⁻⁶) 23 Of these, approximately one trillionth exists, which is about 6.02 × 10⁻⁶ carbon atoms. 11 indivual 14 C. 14 Carbon (C) is known as a radioactive isotope with a half-life of 5730 years, decreasing regularly. All of these decay over a period of 226,000 years. Therefore, it can be assumed that carbon dioxide and other atmospheric substances, after being absorbed and fixed by plants and other organisms, have undergone more than 226,000 years of decay in fossil fuels such as coal, oil, and natural gas. The carbon dioxide contained in these fossil fuels at the time of initial fixation... 14 All carbon (C) decays. Therefore, in the 21st century, fossil fuels such as coal, oil, and natural gas contain absolutely no carbon. 14 Therefore, the chemicals produced using these fossil fuels as raw materials also contain absolutely no carbon (C). 14 C element.
[0147] on the other hand, 14 Carbon is continuously generated in the atmosphere through nuclear reactions caused by cosmic rays, reaching a balance with the reduction based on radioactive decay in Earth's atmospheric environment. 14 The amount of C is constant. Therefore, in the current environment, the matter originating from biomass resources in the material cycle... 14 The C concentration, as described above, is approximately 1 × 10⁻⁶ relative to all C atoms. -12 The values are approximately 10% in moles. Therefore, by using the differences between these values, it is possible to calculate the proportion of compounds derived from natural resources (compounds derived from biomass resources) in a certain compound (rubber) (biomass ratio).
[0148] Typically, the 14 C was determined as described below. Accelerator mass spectrometry based on a tandem accelerator was used for the determination. 13 C concentration ( 13 C / 12 C) 14 C concentration ( 14 C / 12 C) Determination. During the determination, as... 14 The standard reference for carbon concentration is modern carbon, which uses the carbon cycling data in nature as of 1950. 14C concentration. As a specific standard substance, oxalic acid standard provided by NIST (National Institute of Standards and Technology) was used. The radioactivity of carbon in this oxalic acid (carbon content per gram of carbon) was determined. 14 The radioactivity intensity of carbon (C) is classified according to its carbon isotopes. 13 The C-correction is a fixed value, using the value with attenuation correction applied from 1950 AD to the date of measurement as the standard. 14 The C concentration value (100%) is used. The ratio of the actual measured value of the sample to this value is the pMC value.
[0149] Therefore, if the rubber is made entirely from biomass-derived materials, it is expected to have a value of around 110 pMC, despite regional variations (currently, under normal circumstances, it is mostly not 100). On the other hand, for chemicals derived from fossil fuels such as petroleum, the measured value... 14 At C concentrations, the value is around 0 pMC (e.g., 0.3 pMC). This value corresponds to 0% of the biomass ratio mentioned above.
[0150] In summary, from the perspective of contributing to environmental protection and improving sustainability, rubber and other materials with high pMC values are preferably used in rubber compositions.
[0151] (b) Compound materials other than rubber components
[0152] (A) Filler
[0153] As described above, the rubber composition contains silica as a reinforcing filler, but in addition to silica, it may also contain, for example, carbon black, graphite, calcium carbonate, talc, alumina, clay, aluminum hydroxide, mica, etc.
[0154] (i-1)Silica
[0155] From the perspective of achieving good wear resistance and spalling resistance, the BET specific surface area of silica is preferably greater than 140 m². 2 / g, more preferably greater than 160m 2 / g. On the other hand, from the viewpoint of dispersibility in the rubber composition, a dispersion of less than 300m is preferred. 2 / g, more preferably less than 250m 2 / g, more preferably less than 220m 2 / g. Furthermore, the BET specific surface area mentioned above is the N2SA value determined by the BET method according to ASTM D3037-93.
[0156] At this time, the particle size (average primary particle size) of silicon dioxide is preferably 16 nm or less, as described above.
[0157] Examples of silica include dry-process silica (anhydrous silica) and wet-process silica (hydrated silica). Wet-process silica is preferred due to its higher silanol group content. Alternatively, silica made from materials such as aqueous glass or biomass materials such as rice husks can also be used.
[0158] For example, products from Evonik Industries, Rhodia, Tosoh Silicon Chemical Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Co., Ltd., etc., can be used as silicon dioxide.
[0159] There are no particular limitations on the raw materials used for silica. For example, it can be derived from minerals such as quartz, or from biological sources such as rice husks (e.g., silica made from biomass materials such as rice husks). Silica recycled from silica-containing products can also be used. Among these, hydrated silica prepared by a wet process is preferred due to its higher silanol group content.
[0160] Silica obtained from biomass materials, for example, can be extracted from rice husk ash obtained by burning rice husks using sodium hydroxide solution. This silicate is then reacted with sulfuric acid in the same way as conventional wet silica to form silica precipitate, which is then filtered, washed with water, dried, and pulverized to obtain silica.
[0161] Silica recovered from products containing silica can be, for example, silica recovered from products containing silica such as electronic components like semiconductors, tires, desiccants, and filter materials such as diatomaceous earth. Furthermore, the method of recovery is not particularly limited, and examples include thermal decomposition and electromagnetic wave-based decomposition. Of these, silica recovered from electronic components like semiconductors or tires is preferred.
[0162] If silica crystallizes, it becomes insoluble in water and cannot utilize the silicic acid that is its component. By managing the combustion temperature and combustion time, the crystallization of silica in rice husk ash can be suppressed (see Japanese Patent Application Publication No. 2009-2594, Akita Prefectural University Online Journal B, 2019, vol.6, pp.216-222, etc.).
[0163] Amorphous silica extracted from rice husks can be obtained from commercially available materials such as those from Wilmar.
[0164] Furthermore, these silicas can be used alone or in combination with two or more types. Moreover, from the perspective of contributing to environmental protection and improving sustainability, biomass silica and recycled silica are preferred.
[0165] (i-2) Silane coupling agent
[0166] When using the above-mentioned silica, it is preferable to include a silane coupling agent together with the silica.
[0167] As a silane coupling agent, there are no particular limitations; examples include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, and bis(4-triethoxysilylbutyl)tetrasulfide. 3-Trimethoxysilylpropyl disulfide, bis(3-triethoxysilylpropyl) disulfide, bis(2-triethoxysilylethyl) disulfide, bis(4-triethoxysilylbutyl) disulfide, bis(3-trimethoxysilylpropyl) disulfide, bis(2-trimethoxysilylethyl) disulfide, bis(4-trimethoxysilylbutyl) disulfide, 3-trimethoxysilylpropyl-N,N - Dimethylthiocarbamoyl tetrasulfide, 2-triethoxysilylethyl-N,N-dimethylthiocarbamoyl tetrasulfide, 3-triethoxysilylpropyl methacrylate monosulfide, and other sulfide systems; 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, Momentive's NXT and NXT-Z, and other thiol-based systems; vinyltriethoxysilane, vinyltrimethoxysilane, etc. Vinyl-based; amino-based (e.g., 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane); glycidoxy-based (e.g., γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane); nitro-based (e.g., 3-nitropropyltrimethoxysilane, 3-nitropropyltriethoxysilane); chlorine-based (e.g., 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane), among which mercapto-based silane coupling agents are preferred. These can be used alone or in combination of two or more.
[0168] Products from companies such as Evonik Industries, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industries, Azmax, and DuPont Toray Specialty Materials can be used as silane coupling agents.
[0169] The content of the silane coupling agent relative to 100 parts by mass of silicon dioxide is, for example, greater than 3 parts by mass and less than 25 parts by mass.
[0170] (ii) Carbon black
[0171] From the viewpoint of improving wet grip by increasing rigidity and responsiveness, the rubber composition preferably contains carbon black as a reinforcing filler in addition to silica.
[0172] The specific content ratio of carbon black relative to 100 parts by mass of the rubber component is preferably 2 parts by mass or more, more preferably 4 parts by mass or more. On the other hand, it is preferably 15 parts by mass or less, more preferably 12 parts by mass or less.
[0173] As for carbon black, there are no particular limitations. Examples include furnace black such as SAF, ISAF, HAF, MAF, FEF, SRF, GPF, APF, FF, CF, SCF, and ECF; acetylene black; thermal black such as FT and MT; and channel black such as EPC, MPC, and CC. One of these can be used alone, or two or more can be used in combination.
[0174] The preferred CTAB specific surface area (Cetyl Tri-methyl Ammonium Bromide) of carbon black is 130 m². 2 / g or more, preferably 160m 2 / g or more, further preferably 170m 2 / g or more. On the other hand, 250m is preferred. 2 / g or less, more preferably 200m 2 / g or less. Furthermore, the CTAB specific surface area is a value determined according to ASTM D3765-92.
[0175] There are no specific limitations on the specific type of carbon black used; examples include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. Commercially available products include those from Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Corporation, Shin Nippon Chemical Carbon Co., Ltd., and Columbia Carbon Co., Ltd. These can be used individually or in combination of two or more.
[0176] (iii) Other fillers
[0177] In addition to silica and carbon black, the rubber composition may further contain fillers commonly used in the tire industry, such as graphite, calcium carbonate, talc, alumina, clay, aluminum hydroxide, and mica, as needed. The content of these fillers relative to 100 parts by weight of the rubber component is, for example, greater than 0.1 parts by weight and less than 200 parts by weight.
[0178] (B) Plasticizer components
[0179] In rubber compositions, plasticizer components are preferably used as needed to ensure proper dispersion of powdered materials during mixing. Furthermore, plasticizer components here refer to substances that plasticize the rubber composition, such as processing oils, rubber component enhancers, liquid rubber, and resin components.
[0180] These plasticizers can be petroleum-derived substances, biomass-derived substances, or petroleum naphtha recovered from rubber and non-rubber products. Furthermore, low-molecular-weight hydrocarbon components obtained by thermally cracking and extracting used tires and products containing various components can also be used as plasticizers; among these, biomass-derived and recycled plasticizers are preferred as sustainable plasticizers.
[0181] Furthermore, the aforementioned plasticizer can be used alone or in combination of two or more. In this case, the content of the plasticizer component relative to 100 parts by weight of the rubber component is preferably 20 parts by weight or more, more preferably 30 parts by weight or more, and even more preferably 40 parts by weight or more. As an upper limit, for example, it is preferably 100 parts by weight or less, more preferably 80 parts by weight or less, and even more preferably 60 parts by weight or less.
[0182] In addition, the content of plasticizer components also includes the amount of oil contained in rubber (oil-extended rubber), etc.
[0183] (i) Oil
[0184] Examples of oils include mineral oils (usually referring to processing oils), vegetable oils, or mixtures thereof. Examples of mineral oils (processing oils) include paraffinic processing oils, aromatic processing oils, and naphthenic processing oils. Examples of vegetable oils include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice bran oil, safflower oil, sesame oil, olive oil, sunflower seed oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, and tung oil. These can be used alone or in combination of two or more. Furthermore, from a life cycle assessment perspective, refined oils such as waste oil from rubber kneading mixers or automotive engine lubricants, and waste cooking oils can also be used.
[0185] As specific processing oils (mineral oils), products from companies such as Idemitsu Kosan Co., Ltd., Sankyo Oil & Chemical Co., Ltd., ENEOS Co., Ltd., Olisoy Co., Ltd., H&R Co., Ltd., Toyokuni Oil Co., Ltd., Showa Shell Oil Co., Ltd., and Fuji Kosan Co., Ltd. can be used.
[0186] (ii) Liquid rubber
[0187] Liquid rubber, as listed as a plasticizer, refers to polymers that are liquid at room temperature (25°C) and are rubber components that can be extracted from vulcanized tires using acetone. Examples of liquid rubber include farnesene polymers, liquid diene polymers, and their hydrides.
[0188] Farnesene polymers refer to polymers obtained by polymerizing farnesenes, possessing structural units based on farnesenes. Farnesenes include isomers such as α-farnesene ((3E,7E)-3,7,11-trimethyl-1,3,6,10-dodecathetene) and β-farnesene (7,11-dimethyl-3-methylene-1,6,10-dodecathetene).
[0189] Farnesene polymers can be homopolymers of farnesene (farnesene homopolymers) or copolymers of farnesene and vinyl monomers (farnesene-vinyl monomer copolymers).
[0190] Examples of liquid diene polymers include liquid styrene-butadiene copolymer (liquid SBR), liquid butadiene polymer (liquid BR), liquid isoprene polymer (liquid IR), and liquid styrene-isoprene copolymer (liquid SIR).
[0191] The weight-average molecular weight (Mw) of polystyrene-based liquid diene polymers, determined by gel permeation chromatography (GPC), is, for example, greater than 1.0 × 10⁻⁶. 3 Less than 2.0×10 5 Furthermore, in this specification, the Mw of the liquid diene polymer is a polystyrene conversion value determined by gel permeation chromatography (GPC).
[0192] The content of liquid rubber (the total content of liquid farnesene polymers, liquid diene polymers, etc.) is, for example, greater than 1 part by mass and less than 100 parts by mass relative to 100 parts by mass of rubber component.
[0193] As a liquid rubber, products from companies such as Kuraray Corporation and Clayville Corporation can be used.
[0194] (iii) Resin composition
[0195] Resin components can also function as adhesive agents. They can be solid or liquid at room temperature. Specific resin components include, for example, rosin-based resins, styrene-based resins, coumarone-based resins, terpene-based resins, C5 resins, C9 resins, C5C9 resins, and acrylic resins. Among these, C5 and C9 resins are preferred. Specifically, dicyclopentadiene resin (DCPD resin) and AMS resin (α-methylstyrene resin) are examples of such resins. Furthermore, two or more types can be used in combination. Additionally, these resin components can be modified with groups that can react with silica, etc., as needed.
[0196] As described above, the content of the resin component is set to be greater than 55 parts by weight relative to 100 parts by weight of the rubber component, but more preferably greater than 60 parts by weight, and even more preferably greater than 65 parts by weight. As an upper limit, there is no particular limitation, but it is preferably less than 85 parts by weight, more preferably less than 80 parts by weight, even more preferably less than 75 parts by weight, and particularly preferably less than 70 parts by weight.
[0197] Rosin-based resins are resins whose main component is rosin acid, obtained through the processing of rosin. These rosin-based resins (rosin derivatives) can be classified based on whether they are modified or not, into unmodified rosin and modified rosin derivatives. Examples of unmodified rosin include tall oil rosin, resin rosin, wood rosin, disproportionated rosin, polymerized rosin, hydrogenated rosin, and other chemically modified rosin. Modified rosin derivatives are modified forms of unmodified rosin, and examples include rosin esters, unsaturated carboxylic acid-modified rosin derivatives, unsaturated carboxylic acid-modified rosin esters, rosin amide compounds, and rosin amine salts.
[0198] Styrene-based resins are polymers that use styrene-based monomers as constituent monomers. Examples include polymers polymerized with styrene-based monomers as the main component (50% by mass or more). Specifically, in addition to homopolymers formed by homopolymerizing styrene-based monomers (styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, p-methoxystyrene, p-tert-butylstyrene, p-phenylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, etc.), copolymers formed by copolymerizing two or more styrene-based monomers, copolymers of styrene-based monomers with other monomers that can be copolymerized with them can also be listed.
[0199] Examples of other monomers mentioned above include acrylonitriles such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated carboxylic acid esters such as methyl acrylate and methyl methacrylate; dienes such as chloroprene, butadiene, and isoprene; alkenes such as 1-butene and 1-pentene; and α,β-unsaturated carboxylic acids or their anhydrides such as maleic anhydride.
[0200] Among coumarone-based resins, coumarone-indene resin is preferred. Coumarin-indene resin is a resin containing coumarone and indene as monomeric components constituting the resin backbone (main chain). Other monomeric components besides coumarone and indene contained in the backbone include styrene, α-methylstyrene, methylindene, and vinyltoluene.
[0201] The content of coumarin indole resin relative to 100 parts by weight of rubber component is, for example, greater than 1.0 parts by weight and less than 50.0 parts by weight.
[0202] The hydroxyl value (OH value) of coumarin indole resin is, for example, greater than 15 mg KOH / g and less than 150 mg KOH / g. Furthermore, the OH value refers to the amount of potassium hydroxide required, expressed in milligrams, to neutralize the acetic acid bonded to the hydroxyl group when 1 g of the resin is acetylated; this value is determined by potentiometric titration (JIS K 0070:1992).
[0203] The softening point of coumarin indene resin is, for example, greater than 30°C and less than 160°C. Furthermore, the softening point is the temperature at which the ball drops when measured using a ring-and-ball softening point tester as specified in JIS K 6220-1:2001.
[0204] Examples of terpene-based resins include polyterpenes, terpene phenols, and aromatic modified terpene resins. Polyterpenes are resins obtained by polymerizing terpene compounds and their hydrides. Terpene compounds are composed of (C5H8) resins. n The composition of hydrocarbons and their oxygen-containing derivatives is represented by the class of monoterpenes (C64- ... 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 Compounds with terpenes as their basic skeleton include, for example, α-pinene, β-pinene, dipentene, limonene, myrcene, alloocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, and γ-terpineol.
[0205] As polyterpenes, in addition to terpene resins such as α-pinene resin, β-pinene resin, limonene resin, dipentene resin, and β-pinene / limonene resin, which use the aforementioned terpene compounds as raw materials, hydrogenated terpene resins that have undergone hydrogenation treatment of these terpene resins can also be listed. As terpene phenols, resins obtained by copolymerizing the aforementioned terpene compounds with phenolic compounds, as well as resins that have undergone hydrogenation treatment of these resins, can be listed. Specifically, resins obtained by condensing the aforementioned terpene compounds, phenolic compounds, and formaldehyde can be listed. Furthermore, phenolic compounds, for example, phenol, bisphenol A, cresol, xylenol, etc., can be listed. As aromatic modified terpene resins, resins obtained by modifying terpene resins with aromatic compounds, as well as resins that have undergone hydrogenation treatment of these resins, can be listed. Furthermore, as aromatic compounds, there are no particular limitations as long as the compound has an aromatic ring. Examples include phenols such as phenol, alkylphenols, alkoxyphenols, and phenols containing unsaturated hydrocarbon groups; naphthols such as naphthol, alkylnaphthol, alkoxynaphthol, and naphthols containing unsaturated hydrocarbon groups; styrene derivatives such as styrene, alkylstyrene, alkoxystyrene, and styrene containing unsaturated hydrocarbon groups; coumarone, indene, etc.
[0206] "C5 resin" refers to a resin obtained by polymerizing C5 fractions. Examples of C5 fractions include petroleum fractions with 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, and isoprene. Dicyclopentadiene resin (DCPD resin) is particularly preferred as a C5-based petroleum resin.
[0207] "C9 resin" refers to resins obtained by polymerizing C9 fractions, or their hydrogenated or modified products. Examples of C9 fractions include, for example, petroleum fractions with 8 to 10 carbon atoms such as vinyltoluene, alkylstyrene, indene, and methylindene. Specifically, coumarone-indene resin, coumarone resin, indene resin, and aromatic vinyl compound resins are preferred. As aromatic vinyl compound resins, homopolymers of α-methylstyrene (AMS) or styrene, or copolymers of α-methylstyrene and styrene, are preferred for economic reasons, ease of processing, and excellent exothermic properties; copolymers of α-methylstyrene and styrene are more preferred. For example, commercially available substances from companies such as Kraton and Eastman Chemical Company can be used as aromatic vinyl compound resins.
[0208] "C5C9 resin" refers to a resin obtained by copolymerizing the aforementioned C5 fraction and the aforementioned C9 fraction, or it may be a hydrogenated or modified product of them. Examples of C5 and C9 fractions include the aforementioned petroleum fractions. For example, commercially available substances from Tosoh Corporation, LUHUA Corporation, etc., can be used as C5C9 resin.
[0209] There are no particular limitations on the acrylic resin used; for example, solvent-free acrylic resins can be used.
[0210] Solvent-free acrylic resins include (meth)acrylic resins (polymers) synthesized by high-temperature continuous polymerization (high-temperature continuous bulk polymerization) without using polymerization initiators, chain transfer agents, organic solvents, etc., as byproducts (as described in US Patent No. 4,414,370, Japanese Patent Application Publication No. 59-6207, Japanese Patent Application Publication No. 5-58005, Japanese Patent Application Publication No. 1-313522, US Patent No. 5,010,166, and the Toa Synthetic Research Yearbook TREND2000 No. 3, pp. 42-45). Furthermore, in this invention, (meth)acrylic acid refers to methacrylic acid and acrylic acid.
[0211] Examples of monomeric components constituting the above-mentioned acrylic resins include (meth)acrylic acid, (meth)acrylates (alkyl esters, aryl esters, aralkyl esters, etc.), (meth)acrylamide, and (meth)acrylamide derivatives.
[0212] In addition, as monomer components constituting the above-mentioned acrylic resins, besides (meth)acrylic acid and (meth)acrylic acid derivatives, aromatic vinyl compounds such as styrene, α-methylstyrene, vinyltoluene, vinylnaphthalene, divinylbenzene, trivinylbenzene, and divinylnaphthalene can also be used.
[0213] The aforementioned acrylic resins can be resins composed solely of (meth)acrylic acid, or resins that also include components other than (meth)acrylic acid as constituent elements. Furthermore, the aforementioned acrylic resins may also possess hydroxyl, carboxyl, or silanol groups, etc.
[0214] As a resin component, products from companies such as Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Co., Ltd., Rutgers Chemicals, Ltd., BASF, Arizona Chemical Company, Nippon Paint Co., Ltd., Nippon Shokubai Co., Ltd., ENEOS Co., Ltd., Arakawa Chemical Industry Co., Ltd., Taoka Chemical Industry Co., Ltd., etc. can be used.
[0215] (C) Stearic acid
[0216] The rubber composition preferably contains stearic acid. The content of stearic acid relative to 100 parts by weight of the rubber component is, for example, greater than 0.5 parts by weight and less than 10.0 parts by weight. As stearic acid, conventionally known substances can be used, such as products from Nippon Oil Co., Ltd., NOF Corporation, Kao Corporation, Fujifilm, Kojun Pharmaceutical Co., Ltd., Chiba Fatty Acid Co., Ltd., etc.
[0217] (D) Anti-aging agents
[0218] The rubber composition preferably contains an antioxidant. The antioxidant content relative to 100 parts by weight of the rubber component is preferably greater than 0.5 parts by weight and less than 10 parts by weight, more preferably 1 part by weight or more.
[0219] Examples of antioxidants include naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octyl diphenylamine and 4,4′-bis(α,α'-dimethylbenzyl)diphenylamine; p-phenylenediamine-based antioxidants such as N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and N,N'-di-2-naphthyl-p-phenylenediamine; quinoline-based antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol-based antioxidants such as 2,6-di-tert-butyl-4-methylphenol and styreneated phenol; and bis, tri, and polyphenol-based antioxidants such as tetra[methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate]methane. These can be used individually or in combination of two or more.
[0220] In addition, as an anti-aging agent, products from companies such as Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinsei Chemical Co., Ltd., and FLEXSYS can be used.
[0221] (E) Wax
[0222] The rubber composition preferably contains wax. The wax content relative to 100 parts by weight of the rubber component is, for example, 0.5 to 20 parts by weight, preferably 1.0 to 15 parts by weight, and more preferably 1.5 to 10 parts by weight.
[0223] As for waxes, there are no particular limitations. Examples include petroleum-based waxes such as paraffin wax and microcrystalline wax; natural waxes such as plant-based waxes and animal-based waxes; and synthetic waxes such as polymers of ethylene and propylene. These can be used alone or in combination of two or more.
[0224] In addition, as a wax, products from companies such as Ouchi Shinshin Chemical Industry Co., Ltd., Nippon Seiwa Co., Ltd., and Seiko Chemical Co., Ltd. can be used.
[0225] (F) Zinc oxide
[0226] The rubber composition may also contain zinc oxide. The content of zinc oxide is, for example, greater than 0.5 parts by weight and less than 10 parts by weight per 100 parts by weight of the rubber component. As zinc oxide, conventionally known substances can be used, such as products from Mitsui Metal Mining Co., Ltd., Toho Co., Ltd., HAKUSUI TECH Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc.
[0227] (G) Crosslinking agents and vulcanization accelerators
[0228] The rubber composition preferably contains a crosslinking agent such as sulfur. The content of the crosslinking agent is, for example, greater than 0.1 parts by weight and less than 10.0 parts by weight per 100 parts by weight of the rubber component.
[0229] As for sulfur, examples commonly used in the rubber industry include powdered sulfur, settled sulfur, colloidal sulfur, insoluble sulfur, highly dispersed sulfur, and soluble sulfur. These can be used individually or in combination of two or more.
[0230] In addition, products made from companies such as Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., FLEXSYS, Nippon Kanryu Kogyo Co., Ltd., and Hosoi Chemical Industry Co., Ltd. can be used as sulfur.
[0231] Examples of crosslinking agents other than sulfur include sulfur-containing vulcanizing agents such as TACKIROL V200 manufactured by Taoka Chemical Industry Co., Ltd., KA9188 (1,6-bis(N,N'-dibenzylthiocarbamoyldithio)hexane) manufactured by Lanxess Co., Ltd., and organic peroxides such as dicumyl peroxide.
[0232] The rubber composition preferably contains a vulcanization accelerator. The content of the vulcanization accelerator relative to 100 parts by weight of the rubber component is, for example, greater than 0.3 parts by weight and less than 10.0 parts by weight.
[0233] Examples of vulcanization accelerators include thiazole-based accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazole disulfide, and N-cyclohexyl-2-benzothiazole sulfenamide; thiuram-based accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetra(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxoethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based accelerators such as diphenylguanidine, di-o-toluidine, and o-toluidine biguanide. These can be used alone or in combination of two or more.
[0234] (H) Other
[0235] In addition to the components mentioned above, the rubber composition may be further formulated with additives commonly used in the tire industry, such as fatty acid metal salts, carboxylic acid metal salts, organic peroxides, and anti-reversion (vulcanization reversion) agents, as needed. The content of these additives relative to 100 parts by weight of the rubber component is, for example, greater than 0.1 parts by weight and less than 200 parts by weight.
[0236] (2) Preparation of rubber composition
[0237] The tread rubber composition can be appropriately adjusted by adjusting the various compounding materials mentioned above, and can be manufactured by conventional methods, for example, by a manufacturing method including the following steps: a basic kneading step by mixing the rubber components with fillers such as silica and carbon black, and a final kneading step by mixing the mixture obtained in the basic kneading step with a crosslinking agent.
[0238] Mixing can be carried out using known (closed) mixing machines such as Banbury internal mixers, kneaders, and open roll mills.
[0239] The mixing temperature in the basic kneading process is, for example, greater than 50°C and less than 200°C, and the mixing time is, for example, greater than 30 seconds and less than 30 minutes. In addition to the above-mentioned components, in the basic kneading process, compounding agents used in the rubber industry in the past can be added as needed, such as softeners such as oils, zinc oxide, antioxidants, waxes, vulcanization accelerators, etc., and then mixed.
[0240] In the final refining process, the mixture obtained in the basic kneading process is kneaded with a crosslinking agent. The kneading temperature in the final refining process is, for example, above room temperature and below 80°C, and the kneading time is, for example, above 1 minute and below 15 minutes. In addition to the above-mentioned components, vulcanization accelerators, zinc oxide, etc., may be added as needed in the final refining process.
[0241] 2. Tire manufacturing
[0242] The tires involved in this invention can be manufactured as uncured tires by forming a tread rubber of a predetermined shape using a rubber composition obtained above, and then forming it together with other tire components on a tire forming machine using conventional methods.
[0243] Specifically, an uncured tire is manufactured by winding an inner liner (which is a component to ensure the airtightness of the tire), a carcass (which is a component to bear the load, impact and air pressure of the tire), and a belt layer (which is a component to strongly fasten the carcass and improve the tread rigidity) onto a forming drum. A bead portion is also configured to fix the two ends of the carcass to the two side edges and fix the tire to the rim. After being formed into a ring shape, the tire sidewall is formed by attaching the tread to the center of the outer periphery and attaching the sidewall to the radial outer side.
[0244] Furthermore, when the tread layer is configured as a multi-layered structure with the base rubber layer, the rubber composition forming the base rubber layer can be obtained by appropriately varying the mixing ratios of the aforementioned rubber components and compounding materials and performing the same mixing process. Moreover, the tread rubber can be extruded together with the tread rubber layer and formed into a predetermined shape, and then molded together with other tire components on a tire forming machine using conventional methods to produce an uncured tire.
[0245] Then, the uncured tires are heated and pressurized in a vulcanizing machine to obtain tires. The vulcanization process can be carried out using known vulcanization methods. For example, the vulcanization temperature is greater than 120°C and less than 200°C, and the vulcanization time is for example greater than 5 minutes and less than 15 minutes.
[0246] As previously described, the resulting tire exhibits synergistic effects due to proper control of the formulation of the tread rubber composition, the relationship between tread thickness and breaking energy, etc., thereby achieving further improvement in wet grip performance.
[0247] Furthermore, the tires involved in this invention are not limited to a specific classification and can be used as tires for passenger cars, large passenger cars, large SUVs, trucks or buses, two-wheeled vehicles, racing tires, studless anti-skid tires (winter tires), all-season tires, run-flat tires, aircraft tires, mining tires, non-pneumatic tires, etc., but are preferably set as tires for passenger cars.
[0248]
Example
[0249] The following are examples (embodiments) that are considered preferred in practice, but the scope of the invention is not limited to these embodiments.
[0250] The treads formed from the various compound materials shown below, as well as tires composed of other rubber components, were studied. The results of the calculations based on the evaluation methods described below are shown in the lower part of Tables 2 and 3 regarding wear resistance, blockage resistance, and the combined performance of both.
[0251] 1. A rubber composition forming the rubber layer of the driving surface.
[0252] Rubber compositions are made using the various compounding materials shown below to form the tread rubber layer of the tire tread.
[0253] (1) Compounding materials
[0254] (a) Rubber composition
[0255] (A) NR: TSR-20
[0256] (B) SBR-1: Modified S-SBR manufactured based on the following manufacturing example (styrene content: 20% by mass, vinyl content: 20% by mol%, Tg: -60°C, Mw: 650,000).
[0257] (C) SBR-2: SSBR HPR850 manufactured by ENEOS MATERIALS (styrene content: 26% by mass, vinyl content: 59% by mol%, Tg: -25°C, non-oil-extended).
[0258] (D)BR: Ube Industries UBEPOL BR150B (high-cision BR) manufactured by Ube Industries.
[0259] (cis content 97% by mass, trans content 2% by mass, vinyl content 1% by mass)
[0260] (Manufacturing Example 1: Manufacturing of SBR-1)
[0261] The SBR-1 described above was prepared according to the following steps. First, cyclohexane, tetrahydrofuran, styrene, and 1,3-butadiene were added to a nitrogen-purged autoclave reactor. After adjusting the temperature of the reactor contents, n-butyllithium was added to initiate polymerization. Then, polymerization was carried out under adiabatic conditions. At the point where the polymerization conversion reached 99%, 1,3-butadiene was added to further polymerize for 5 minutes. 3-Dimethylaminopropyltriethoxysilane was added as a modifier to continue the reaction. After the polymerization reaction was completed, 2,6-di-tert-butyl-p-cresol was added, and the solvent was removed by steam stripping. The product was then dried using hot rollers to obtain SBR-1.
[0262] (b) Compound materials other than rubber components
[0263] (A) Silica: ULTRASIL 9100Gr manufactured by Evonik Industries
[0264] (N2SA: 235m) 2 / g, average particle size: 15nm)
[0265] (B) Silane coupling agent-1: Si266 manufactured by Evonik Industries
[0266] (bis(3-triethoxysilylpropyl)disulfide)
[0267] (C) Silane coupling agent-2: NXT manufactured by Momentive
[0268] (3-Octaylthiopropyltriethoxysilane)
[0269] (D) Carbon black: DIABLACK N220 manufactured by Mitsubishi Chemical Corporation
[0270] (N2SA: 115m) 2 / g)
[0271] (E) Resin composition: PR383 manufactured by Exxon Mobil
[0272] (Hydrogenated DCPD / C9 resin, softening point: 100℃)
[0273] (F) Oil: Vivatec 500 manufactured by H&R.
[0274] (Aromatic processing oil: TDAE oil)
[0275] (G) Zinc oxide: Zinc oxide No. 2 manufactured by Mitsui Metals Mining Co., Ltd.
[0276] (H) Antioxidant-1: Antigen 6C manufactured by Sumitomo Chemical Co., Ltd.
[0277] (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine)
[0278] (I) Antioxidant-2: ANTAGE RD manufactured by Kawaguchi Chemical Co., Ltd.
[0279] (2,2,4-Trimethyl-1,2-Dihydroquinoline polymer)
[0280] (J) Stearic acid: TSUBAKI stearic acid beads manufactured by Nippon Oil Company.
[0281] (K) Wax: OZOACE 0355 manufactured by Nippon Fine Wax Co., Ltd.
[0282] (L) Sulfur: Powdered sulfur (containing 5% oil) manufactured by Tsurumi Chemical Industry Co., Ltd.
[0283] (M) Vulcanization Accelerator-1: NOCCELER CZ manufactured by Ouchi Shinshin Chemical Industry Co., Ltd.
[0284] (N-Cyclohexyl-2-benzothiazole sulfenamide (CBS))
[0285] (N) Vulcanization accelerator-2: NOCCELER DPG manufactured by Ouchi Shinshin Chemical Industry Co., Ltd.
[0286] (Diphenylguanidine (DPG))
[0287] (2) Manufacturing of rubber composition
[0288] Based on the formulations shown in Tables 2 and 3, the materials other than sulfur and vulcanization accelerator were mixed at 150°C for 5 minutes using a 1.7L Banbury internal mixer manufactured by Kobe Steel to obtain the mixture.
[0289] Then, sulfur and vulcanization accelerator are added to the mixture, and it is kneaded for 5 minutes at 80°C using an open rolling mill to obtain a rubber composition that forms the rubber layer on the driving surface.
[0290] 2. Manufacturing of the rubber composition forming the base rubber layer
[0291] At the same time, the rubber composition forming the base rubber layer is also based on the formulation shown in Table 1, and the same as the rubber composition forming the driving surface rubber layer is used to obtain the rubber composition forming the base rubber layer.
[0292] Table 1
[0293]
[0294] 3. Manufacturing of pneumatic tires
[0295] Using various rubber compositions, a tread having a tread rubber layer and a base rubber layer is formed into a specified shape.
[0296] Then, it is bonded together with other tire components to form an uncured tire, and then vulcanized under pressure at 170°C for 10 minutes to manufacture the test tires of Examples 1-6 and Comparative Examples 1-6 shown in Tables 2 and 3 (tire size: 255 / 45R22, aspect ratio: 45%, negative profile ratio: 33%, tread thickness: 3mm, tread thickness: 12.5mm, tread ratio: 24%).
[0297] 4. Properties of vulcanized rubber
[0298] Then, viscoelasticity test samples (20 mm long × 4 mm wide × 1 mm thick) were collected from the interior of the tread rubber layer of each test tire, with the tire circumference as the long side. Using GABO's "EPLEXOR" series viscoelasticity testers, the loss tangent (tanδ) was measured at various test temperatures (0℃, -20℃, -30℃, -40℃) under the conditions of a frequency of 10 Hz, initial strain of 5%, dynamic strain rate of 1%, and deformation mode of tension. Simultaneously, the complex elastic modulus (E0℃) was measured under the conditions of a temperature of 0℃, a frequency of 10 Hz, an initial strain of 5%, a dynamic strain rate of 1%, and deformation mode of elongation. * Furthermore, the thickness of the sample is oriented radially towards the tire. Additionally, when the same formulation is used in multiple embodiments, the thickness is the average of values measured from each test tire.
[0299] Furthermore, the glass transition temperature (Tg) of each sample was determined using the same method as for the SBR described above. Specifically, it was determined from the temperature distribution curve of the loss tangent (tanδ) measured using a viscoelasticity measuring device from the "EPLEXOR" series manufactured by GABO. Specifically, the temperature distribution curve of tanδ was measured under the conditions of a frequency of 10 Hz, initial strain of 10%, amplitude ±0.5%, and heating rate of 2 °C / min. The temperature corresponding to the maximum tanδ value in the range above -60 °C and below 40 °C was set as the glass transition temperature.
[0300] Furthermore, if there are two or more points with the maximum tanδ value within the range of -100℃ to 40℃, the point with the lowest temperature is set as the glass transition temperature. For example, if the peak value of tanδ is within the range of -100℃ to 40℃, then according to the above definition, this peak temperature is the glass transition temperature. Additionally, for example, if a temperature distribution curve is obtained where the peak value of tanδ is in the region below -100℃ and tanδ gradually decreases with increasing temperature within the range of -100℃ to 40℃, then according to the above definition, the glass transition temperature is -100℃.
[0301] Then, calculate B1, B1 × driving surface ratio, SBR amount × flatness ratio, silica amount / negative profile ratio, and resin component amount / negative profile ratio.
[0302] 5. Performance evaluation test
[0303] (1) Evaluation of wear resistance
[0304] The test tires were installed on all wheels of the vehicle, and the vehicle was driven on a test route on dry asphalt. The groove depth of the tire tread was measured after driving a specified distance, and the distance traveled when the tire groove depth decreased by 1 mm was calculated.
[0305] Then, taking the result from Comparative Example 1 as 100, and exponentializing it based on the following formula, we set it as an evaluation of wear resistance. The larger the value, the better the wear resistance.
[0306] Abrasion resistance = [(Result of the test tire) / (Result of Comparative Example 1)] × 100
[0307] (2) Resistance to chipping
[0308] Each test tire was assembled onto a standard rim, inflated to the standard internal pressure (250 kPa), and then installed on all wheels of the test vehicle (2000 cc displacement, front-wheel drive). The vehicle was driven on an unpaved road at 50 km / h for 4 hours. Then, for all cracks that appeared on the tire surface, their circumferential length was measured, and the maximum value was determined.
[0309] Then, the result from Comparative Example 1 is taken as 100 and exponentialized based on the following formula as an evaluation of the resistance to block shearing. The larger the value, the better the resistance to block shearing.
[0310] Block resistance = [(Result of Comparative Example 1) / (Result of the test tire)] × 100
[0311] Table 2
[0312]
[0313] Table 3
[0314]
[0315] The present invention has been described above based on embodiments, but the present invention is not limited to the embodiments described above. Various modifications can be made to the above embodiments within the same and equivalent scope as the present invention.
[0316] The present invention (1) is a tire, characterized in that,
[0317] It is a tire with a tread.
[0318] The tread portion has a tread rubber layer with a thickness (mm) formed at a ratio C (%) relative to the total thickness (mm) of the tread portion.
[0319] The rubber layer of the driving surface is formed using a rubber composition that contains less than 25% by mass of styrene-butadiene rubber (SBR) in the rubber component, and, relative to 100 parts by mass of the rubber component, contains more than 90 parts by mass of silica and more than 55 parts by mass of resin component.
[0320] The complex elastic modulus of the rubber layer on the driving surface is 0°E. * The loss tangent (tanδ) of the rubber layer at 0℃ and -20℃ tanδ (tanδ, -30℃ tanδ, -40℃ tanδ) satisfies the following equation (1), and the complex elastic modulus at 0℃ E *The loss tangent (tanδ at 0℃, -20℃, -30℃, and -40℃) of the rubber layer of the driving surface was measured at a temperature of 0℃, a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of elongation. The loss tangent (tanδ at 0℃, -20℃, -30℃, and -40℃) was also measured at a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of tension, at temperatures of 0℃, -20℃, -30℃, and -40℃.
[0321] The B1 shown in equation (1) below and the ratio C (%) satisfy the following equation (2).
[0322] B1[={(-40℃tanδ)+(-30℃tanδ)+(-20℃tanδ)}×0℃tanδ / 0℃E * ]≥0.060 (1)
[0323] B1×C>1.0 (2)
[0324] This invention (2) is the tire described in this invention (1), characterized in that,
[0325] The value B1 is greater than 0.065.
[0326] This invention (3) is the tire described in this invention (2), characterized in that,
[0327] The value B1 is greater than 0.070.
[0328] The present invention (4) is a tire of any combination of any one of the present inventions (1) to (3), characterized in that,
[0329] The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 20% by mass.
[0330] The present invention (5) is the tire described in the present invention (4), characterized in that,
[0331] The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 15% by mass.
[0332] The present invention (6) is a tire of any combination of any one of the present inventions (1) to (5), characterized in that,
[0333] The product of the content (parts by mass) of styrene-butadiene rubber (SBR) in 100 parts by mass of the rubber component and the aspect ratio (%) of the tire is greater than 2000.
[0334] The present invention (7) is a tire of any combination of any one of the present inventions (1) to (6), characterized in that,
[0335] The ratio of the content (parts by mass) of silica relative to 100 parts by mass of the rubber component to the negative profile ratio (%) of the tread surface is greater than 3.
[0336] The present invention (8) is a tire of any combination of any one of the present inventions (1) to (7), characterized in that,
[0337] The average particle size of the silica is less than 16 nm.
[0338] The present invention (9) is a tire of any combination of any one of the present inventions (1) to (8), characterized in that,
[0339] The resin component is dicyclopentadiene resin or α-methylstyrene resin.
[0340] The present invention (10) is a tire of any combination of any one of the present inventions (1) to (9), characterized in that,
[0341] The product of the value B1 and the ratio (%) of the thickness of the driving surface rubber layer to the thickness of the tread surface is greater than 1.5.
[0342] The present invention (11) is a tire of any combination of any one of the present inventions (1) to (10), characterized in that,
[0343] The rubber composition contains a mercapto-based silane coupling agent.
[0344] This invention (12) is a tire of any combination of any one of the claims (1) to (11) of this invention, characterized in that,
[0345] The content of styrene-butadiene rubber (SBR) in 100 parts by weight of the rubber component is greater than 50 parts by weight.
[0346] The present invention (13) is a tire of any combination of any one of the present inventions (1) to (12), characterized in that,
[0347] The rubber composition contains isoprene-based rubber as a rubber component.
[0348] The present invention (14) is a tire of any combination of any one of the claims (1) to (13) of the present invention, characterized in that,
[0349] The silica content in the rubber composition is less than 190 parts by weight relative to 100 parts by weight of the rubber component.
Claims
1. A tire, characterized in that, It is a tire with a tread. The tread portion has a running surface rubber layer with a thickness in a ratio C relative to the total thickness of the tread portion. The rubber layer of the driving surface is formed using a rubber composition that contains less than 25% by weight of styrene-butadiene rubber (SBR) in the rubber component, and, relative to 100 parts by weight of the rubber component, contains more than 90 parts by weight of silica and more than 55 parts by weight of resin component. The complex elastic modulus of the rubber layer on the driving surface is 0°E. * The loss tangents of the rubber layer at 0℃tanδ, -20℃tanδ, -30℃tanδ, and -40℃ satisfy the following equation (1), and, The B1 shown in equation (1) and the ratio C satisfy equation (2). B1[={(-40℃tanδ)+(-30℃tanδ)+(-20℃tanδ)|×0℃tanδ / 0℃E * ]≥0.060 (1), B1×C>1.0 (2) The thickness is in mm, the ratio C is in %, and the complex elastic modulus E is... * The unit is MPa; The complex elastic modulus at 0°C E * The measurements were taken at a temperature of 0℃, a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of elongation. The loss tangents 0℃tanδ, -20℃tanδ, -30℃tanδ, and -40℃tanδ were measured at temperatures of 0℃, -20℃, -30℃, and -40℃, respectively, under the conditions of a frequency of 10Hz, an initial strain of 5%, a dynamic strain rate of 1%, and a deformation mode of tension.
2. The tire according to claim 1, characterized in that, The value B1 is greater than 0.
065.
3. The tire according to claim 2, characterized in that, The value B1 is greater than 0.
070.
4. The tire according to any one of claims 1 to 3, characterized in that, The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 20% by mass.
5. The tire according to claim 4, characterized in that, The styrene content of the styrene-butadiene rubber (SBR) in the rubber composition is less than 15% by mass.
6. The tire according to any one of claims 1 to 3, characterized in that, The product of the styrene-butadiene rubber (SBR) content in 100 parts by mass of the rubber component and the tire aspect ratio is greater than 2000. The unit of the content is parts by mass, and the unit of the flatness is %.
7. The tire according to any one of claims 1 to 3, characterized in that, The ratio of the silica content relative to 100 parts by mass of the rubber component to the negative profile ratio on the tread surface is greater than 3. The unit of the content is parts by mass, and the unit of the negative profile ratio is %.
8. The tire according to any one of claims 1 to 3, characterized in that, The average particle size of the silica is less than 16 nm.
9. The tire according to any one of claims 1 to 3, characterized in that, The resin component is dicyclopentadiene resin or α-methylstyrene resin.
10. The tire according to any one of claims 1 to 3, characterized in that, The product of the value B1 and the ratio of the thickness of the tread rubber layer to the thickness of the tread portion is greater than 1.
5. The unit of the ratio is %.
11. The tire according to any one of claims 1 to 3, characterized in that, The rubber composition contains a mercapto-based silane coupling agent.
12. The tire according to any one of claims 1 to 3, characterized in that, The content of styrene-butadiene rubber (SBR) in 100 parts by weight of the rubber component is greater than 50 parts by weight.
13. The tire according to any one of claims 1 to 3, characterized in that, The rubber composition contains isoprene-based rubber as a rubber component.
14. The tire according to any one of claims 1 to 3, characterized in that, The silica content in the rubber composition is less than 190 parts by mass relative to 100 parts by mass of the rubber component.
15. The tire according to any one of claims 1 to 3, characterized in that, The styrene-butadiene rubber (SBR) in the rubber composition has a styrene content of 3% by mass or more.
16. The tire according to any one of claims 1 to 3, characterized in that, The content of styrene-butadiene rubber (SBR) in 100 parts by weight of the rubber component is less than 90 parts by weight.
17. The tire according to any one of claims 1 to 3, characterized in that, The content of the resin component is less than 85 parts by mass relative to 100 parts by mass of the rubber component.
Citation Information
Patent Citations
Bulk polymerization and polymer
JP1984006207A
Catalytic lumpy production of cyclic ester modified acrylic polymer
JP1989313522A
Bulk polymerization for manufacturing high solid content homogeneous copolymer
JP1993058005B2
Small combustion furnace for manufacturing rice husk ash
JP2009002594A
Rubber composition and tire
JP2010111753A